The male brain - Brizendine, Louann, 1952- (New York : Broadway Books, 2010)
Identifies gender differences in the brain, behavior, and hormones to reveal the fundamental characteristics of male realities, offering insight into such topics as the male problem-solving process, competitive aptitude, and sexual drive.
Keywords: Neuroendocrinology; Brain -- Sex differences; Men -- Physiology; Brain; Sex differences (Psychology); Men -- Physiology